2001
DOI: 10.1007/s002130100793
|View full text |Cite
|
Sign up to set email alerts
|

Withdrawal from chronic morphine administration causes prolonged enhancement of immobility in rat forced swimming test

Abstract: The results suggest that the morphine withdrawal resulted in prolonged enhancement of depression-like behavior in drug-dependent laboratory animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 21 publications
3
34
0
Order By: Relevance
“…Thus, these results suggested that prolonged morphine withdrawal induced depressive-like behaviors, and these depressive-like behaviors were increased along with the duration of abstinence. These findings are consistent with previous studies linking morphine abstinence and depressive-like behaviors [7,8,53,54]. In addition, these findings are broadly consistent with former work showing that the depressive-like behaviors developed after cocaine and ethanol withdrawal [10,29].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, these results suggested that prolonged morphine withdrawal induced depressive-like behaviors, and these depressive-like behaviors were increased along with the duration of abstinence. These findings are consistent with previous studies linking morphine abstinence and depressive-like behaviors [7,8,53,54]. In addition, these findings are broadly consistent with former work showing that the depressive-like behaviors developed after cocaine and ethanol withdrawal [10,29].…”
Section: Discussionsupporting
confidence: 92%
“…These neuropsychiatric disorders, in particular depression, induced by opiate withdrawal, have been shown to trigger craving and relapse [5,6]. Consistent with the human reports, animal studies also indicated that abstinent mice developed depressive-like deficits [7][8][9][10]. These findings provided direct links between opiate withdrawal and depressive-like behaviors, however, the molecular mechanism underlying opiate withdrawal-induced depression remains unclear.…”
Section: Introductionmentioning
confidence: 56%
“…These manipulations include a genetic predisposition; 82,228 exposure to early life stressors, 229 chronic stress, 230-232 prenatal stress; 233 being in the postpartum state; 234 immunological activation; 235,236 or deprivation of dietary tryptophan. 237 In addition, withdrawal from morphine, amphetamine and phencyclidine, which in humans has been associated with depressive-like behavior, has been shown to increase immobility in the FST in rats and mice 77,[238][239][240] and to affect intercranial selfstimulation (ICSS), 240 which further supports the use of this parameter to detect depression-like behavior and indicating the etiological validity of these paradigms. 205 Honey!…”
Section: Animal Model Of Depression or Of Antidepressant Action?mentioning
confidence: 68%
“…In their view this model rather mimics Parkinson's disease associated depression (Skalisz et al, 2002). Recently, withdrawal from drugs like amphetamines, which in humans may cause a depressive syndrome, has been shown to increase immobility in the forced swim test and to affect intracranial self-stimulation in rodents (Cryan et al, 2003;Anraku et al, 2001;Noda et al, 2000). Therefore, amphetamine withdrawal has been proposed as a measure for inducing depression in rodents (Cryan et al, 2003;Barr and Phillips, 1999;Lynch and Leonard, 1978).…”
Section: Animal Models Of Depressionmentioning
confidence: 95%